2021
DOI: 10.32942/osf.io/eu6rx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astatotilapia species (Teleostei, Cichlidae) from Malawi, Mozambique and Tanzania, excluding the basin of Lake Victoria.

Abstract: The haplochromine cichlid fauna of the rivers and smaller lakes of Tanzania and SE Africa are of key importance in understanding the origins and inter-relationships of the great lake cichlid radiations of Malawi, Tanganyika and Victoria. Prior to formal taxonomic investigations, here we present the results of investigations of the type specimens, identification of type localities and superficial characterisation of freshly-collected material. The type locality of Astatotilapia bloyeti (Sauvage, 1883) is identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The original description mentioned "Kinganiflusse in Deutsch-Ostrafrika," and subsequent authors indicated the type locality as the Kingani River at Dunda (Boulenger, 1909;Poll, 1967;Zarske, 2011). The Kingani River is an alternative name for the southern Ruvu River, with annotations of Stuhmann's 1890 expedition indicating Dunda near the current Mtoni Fort, west of Bagamoyo, eastern Tanzania (Turner et al, 2021). Thus, we herein consider the type locality of Petersius con- Petersius conserialis is seemingly endemic to lowland regions of the Rufiji and Ruvu rivers in the Pwani Region of eastern Tanzania (fig.…”
Section: Petersius Hilgendorf 1894mentioning
confidence: 94%
“…The original description mentioned "Kinganiflusse in Deutsch-Ostrafrika," and subsequent authors indicated the type locality as the Kingani River at Dunda (Boulenger, 1909;Poll, 1967;Zarske, 2011). The Kingani River is an alternative name for the southern Ruvu River, with annotations of Stuhmann's 1890 expedition indicating Dunda near the current Mtoni Fort, west of Bagamoyo, eastern Tanzania (Turner et al, 2021). Thus, we herein consider the type locality of Petersius con- Petersius conserialis is seemingly endemic to lowland regions of the Rufiji and Ruvu rivers in the Pwani Region of eastern Tanzania (fig.…”
Section: Petersius Hilgendorf 1894mentioning
confidence: 94%
“…These included Astatotilapia gigliolli (n=2) and Astatotilapia sp. 'Ruaha blue' (n=2), native to the Great Ruaha River 66,67 . Construction of a mtDNA-based phylogeny initially placed Astatotilapia sp.…”
Section: Astatotilapia Calliptera and Ruaha Catchmentmentioning
confidence: 99%
“…Astatotilapia is polyphyletic and current members of the genus are widespread across East and North Africa 6,66,67 . Only one species of Astatotilapia is native to Lake Malawi, Astatotilapia calliptera , which is also found in East African rivers flowing eastward to the Indian Ocean, from the Rovuma River in the north, to the Save River in the south.…”
Section: Data Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original generic description was based on two species, Ctenochromis pectoralis Pfeffer, 1893 and Ctenochromis strigigena Pfeffer, 1893. The latter was then synonymised with Astatotilapia bloyeti (Sauvage, 1883) by Regan (1922a), which remains the situation until today (Turner et al 2021). While regarding Ctenochromis as a junior synonym of Haplochromis Hilgendorf, 1888, Regan (1922a) also designated the type species as Ctenochromis pectoralis Pfeffer, 1893.…”
Section: Introductionmentioning
confidence: 99%